2011
DOI: 10.1111/j.1553-2712.2011.01233.x
|View full text |Cite
|
Sign up to set email alerts
|

A Research Agenda to Assure Equity During Periods of Emergency Department Crowding

Abstract: The effect of emergency department (ED) crowding on equitable care is the least studied of the domains of quality as defined by the Institute of Medicine (IOM). Inequities in access and treatment throughout the health care system are well documented in all fields of medicine. While there is little evidence demonstrating that inequity is worsened by crowding, theory and evidence from social science disciplines, as well as known barriers to care for vulnerable populations, would suggest that crowding will worsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 48 publications
0
19
0
1
Order By: Relevance
“…Overcrowding could affect treatment received and may increase differential treatment by reducing empathy toward disadvantaged groups. [11] Implicit bias has also been shown to be present within the ED setting for AI children and may lead to differential care, especially in the face of a busy ED. [12]…”
mentioning
confidence: 99%
“…Overcrowding could affect treatment received and may increase differential treatment by reducing empathy toward disadvantaged groups. [11] Implicit bias has also been shown to be present within the ED setting for AI children and may lead to differential care, especially in the face of a busy ED. [12]…”
mentioning
confidence: 99%
“…Crowding may place physicians under information overload, 25 a state in which they are more likely to both commit errors and attempt escape from difficult tasks, 26 suggesting the potential for an increase in potentially avoidable admissions as ED physicians choose admission as a safe alternative for these gray area patients. One previous study has examined this association and found an association between crowding and increased likelihood of admission for transient ischemic attack patients in Canada; 27 to our knowledge this association has not been in investigated among all patients or in the United States.…”
mentioning
confidence: 99%
“…For example, some evidence suggests that injury severity varies by race, thus warranting differential use of ADI [35, 37]. In addition, the extent of overcrowding in an ED has been shown to affect the thoroughness of patients’ evaluation, which disproportionately affects hospitals that serve higher number of African Americans [37, 38]. Other potential explanations for racial differences in ADI use include provider implicit bias [35], and/or potential overuse of ADI in white patients rather than underuse by African American patients [39].…”
Section: Discussionmentioning
confidence: 99%